Performance evaluation of industrial ethernet protocols for real-time fault detection based adaptive observer in networked control systems with network communication constraints - Herve, Samba Aime; Tamtsia Aurelien, Yeremou; Nneme Leandre, Nneme (IAES International Journal of Robotics and Automation (IJRA), 2021)
In this paper, the performance evaluation of industrial ethernet (EtherNet/IP, EtherCAT and PROFINET IRT) networks has been studied for choosing the right protocol in real-time fault detection based adaptive sliding mode observer in networked control systems (NCSs) under time network-induced delays, stochastic packet losses, access constraints and bounded disturbances. An adaptive sliding-mode observer based fault detection is presented. The dynamic hydroelectric power plant model is used to verify the effectiveness of the proposed method based on TrueTime and Matlab/ Simulink, corroborated our predictions that an ethernet for control automation technology (EtherCAT) protocol would be more appropriate to reduce the false alarm rate and increasing the efficiency of the remote control of industrial hydroelectric power plant.